2011
DOI: 10.1186/1471-5945-11-7
|View full text |Cite
|
Sign up to set email alerts
|

Original article title: "Comparison of therapeutic efficacy of topical corticosteroid and oral zinc sulfate-topical corticosteroid combination in the treatment of vitiligo patients: a clinical trial"

Abstract: BackgroundVitiligo is the most prevalent pigmentary disorder which occurs worldwide, with an incidence rate between 0.1-4 percent. It is anticipated that the discovery of biological pathways of vitiligo pathogenesis will provide novel therapeutic and prophylactic targets for future approaches to the treatment and prevention of vitiligo. The purposes of this study were evaluating the efficacy of supplemental zinc on the treatment of vitiligo.MethodsThis randomized clinical trial was conducted for a period of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 29 publications
1
51
1
3
Order By: Relevance
“…For the first time, as a hypothesis, Bagherani and colleagues suggested that there might be association between this glycoprotein and vitiligo, which should be confirmed (Bagherani, 2011(Bagherani, , 2012aBagherani et al, 2011;Yaghoobi et al, 2011a).…”
Section: Etiology and Pathogenesis Of Vitiligomentioning
confidence: 99%
See 4 more Smart Citations
“…For the first time, as a hypothesis, Bagherani and colleagues suggested that there might be association between this glycoprotein and vitiligo, which should be confirmed (Bagherani, 2011(Bagherani, , 2012aBagherani et al, 2011;Yaghoobi et al, 2011a).…”
Section: Etiology and Pathogenesis Of Vitiligomentioning
confidence: 99%
“…For the first time, Bagherani and colleagues revealed that oral zinc can be effective in treatment of vitiligo Yaghoobi et al, 2011a).…”
Section: Other Complementary Modalitiesmentioning
confidence: 99%
See 3 more Smart Citations